Alinhamento de seqüências biológicas com o uso de algoritmos genéticos - Ogata, Sabrina Oliveira (Universidade Federal de São Carlos, 2005)
The comparison of genome sequences from different organisms is one of the computational application most frequently used by molecular biologists. This operation serves as support for other processes as, for instance, the determination of the three- dimensional structure of the proteins. During the last years, a significative increase has been observed in the use of Genetic Algorithms (GA) for optimization problems as, for example, dna or protein sequence alignment. GAs are search techniques inspired in mechanisms from Natural Selection and Genetics. In this work, a GA was used to development a computacional tool for the sequence alignment problem. A benchmark comparison of this program with the bl2seq tool (from Blast package) is showed using some sequences, varying in similarity and length. In some cases the GA overhelmed the bl2seq tool. This work contributes to the Bioinformatic field by the use of a novel methodology that can use as an option for sequence analysis in genome projects and to enhance the results of other tools such like Blast.
Keywords: Genética processamento de dados; Bioinformática; Algoritmos genéticos; Alinhamento de seqüências; Genetic algorithms; Pairwise alignment; Bioinformatics; CIENCIAS BIOLOGICAS::GENETICA